Effect of Extreem Rainfall Pattern on The Growth and Yield of Chili Peppers - Wini Prayogi Abdila; Bayu Dwi Apri Nugroho; Chandra Setyawan (The University of Lampung, 2022)
The purpose of this study was to observe the effect of extreme rainfall patterns in the DI Yogyakarta region on the growths of rawit/cayenne (Capsicum frutescens L.) and keriting/curly (Capsicum annum) chili peppers. The experimental design used was Randomized Complete Block Design (RCBD) with single factor consisting of three levels namely: maximum frequency index (P1), rainfall intensity index (P2), and control treatment (K). The frequency and intensity indexes (P1 and P2) of May-June-July from each weather station were used as the bases of rainfall simulations applied in watering the rawit and keriting chili pepper cultivations. Whilst, control (K) was the watering on the basis of optimum crop water requirement. The growth parameters observed included plant height, number of leaves, age of flowering, age of fruiting, age of first harvest, final weight of biomass, and yield. The data sets were analyzed by using one-way Analysis of Variance (ANOVA) at α=0.05 for each species. The results showed that the three levels of treatments did not significantly affect the growth and yield based on all parameters observed for both of the two species. So even the potted media were flooded, the water easily drained through the holed base of pots, making plant growth undisturbed. This finding suggested that planting chili peppers in pots or elevated media could mitigate the effect of extreme rainfalls.Keywords: Extreme Precipitation, Extreme Indices, Plant Growth, chili pepper